Оптимізація діагностичних та реабілітаційних заходів у відновному періоді геморагічного півкульового інсульту - Дронова, Анастасія Олександрівна; Dronova, A. O. (Запорізький державний медико-фармацевтичний університет, 2023)
Дисертаційна робота присвячена удосконаленню діагностики та підвищенню ефективності реабілітації хворих на геморагічний півкульовий інсульт на етапі відновного періоду захворювання шляхом виявлення клініко-неврологічних, нейропсихологічних та нейрофізіологічних особливостей та оптимізації лікування за допомогою використання комбінованої нейрометаболічної терапії. Для досягнення поставленої мети нами було проведено відкрите, когортне, контрольоване дослідження 97 хворих (медіана віку хворих була 58 (52; 63) років) на геморагічний півкульовий інсульт впродовж відновного періоду захворювання, яке включало оцінювання клініко-неврологічних даних, нейропсихологічного тестування, показників якості життя, параметрів спектрального аналізу біоелектричної активності головного мозку із подальшою оптимізацією реабілітаційних заходів. The dissertation is devoted to improving diagnostics and increasing efficiency of rehabilitation of patients with haemorrhagic hemispheric stroke during the recovery period of the disease by identifying clinical-neurological, neuropsychological and neurophysiological features and optimizing treatment using combined neurometabolic therapy. To achieve this goal, we conducted an open, cohort, controlled study of 97 patients (median age of patients was 58 (52; 63) years) with haemorrhagic hemispheric stroke during the recovery period of the disease, which included evaluation of clinical and neurological data, neuropsychological testing, quality indicators of life, parameters of spectral analysis of brain bioelectric activity with further optimization of rehabilitation measures. According to the results of a complex clinical and neurological study with a specially developed protocol, the clinical features of the course of the early recovery period in patients with HHS were determined. It was set that on the 30th day of the disease, the average NIHSS score was 8 (5.75; 10), mRS 3 (2; 3) points, and BI – 70 (60; 85) points. A reliable positive dynamics of the recovery of indicators according to the NIHSS, mRS, BI scales on the 90th, 180th and 360th day of the disease was revealed (р˂0.05). The relationship between the indicators of the level of self-care in patients on the 360th day of HHS and the severity of stroke on the 30th day of the disease (R= –0.713, р˂0.01) and the presence of manifestations of spasticity in paretic muscles (R= –0.375, p˂0.05).
Optimization of diagnostic and rehabilitation measures in the recovery period of haemorrhagic hemispheric stroke
Keywords: інсульт; геморагічний інсульт; реабілітація; відновний період; неврологічний дефіцит; якість життя; когнітивні функції; когнітивні порушення (розлади); психоемоційний стан; депресивні розлади; тривожні розлади; відновлення; електроенцефалографія; нейрометаболічна терапія; stroke; haemorrhagic stroke; rehabilitation; recovery period; neurological deficit; quality of life; cognitive functions; cognitive disorders (disorders); psychoemotional state; depressive disorders; anxiety disorders; recovery; electroencephalography; neurometabolic therapy